Haematopoietic stem cell transplantation for severe autoimmune diseases in children: A review of current literature, registry activity and future directions on behalf of the autoimmune diseases and paediatric diseases working parties of the European Society for Blood and Marrow Transplantation. (27th April 2022) - Achini‐Gutzwiller, Federica R.; Snowden, John A.; Corbacioglu, Selim; Greco, Raffaella; ,
Summary: Although modern clinical management strategies have improved the outcome of paediatric patients with severe autoimmune and inflammatory diseases over recent decades, a proportion will experience ongoing or recurrent/relapsing disease activity despite multiple therapies often leading to irreversible organ damage, and compromised quality of life, growth/development and long‐term survival. Autologous and allogeneic haematopoietic stem cell transplantation (HSCT) have been used successfully to induce disease control and often apparent cure of severe treatment‐refractory autoimmune diseases (ADs) in children. However, transplant‐related outcomes are disease‐dependent and long‐term outcome data are limited in respect to efficacy and safety. Moreover, balancing risks of HSCT against AD prognosis with continually evolving non‐transplant options is challenging. This review appraises published literature on HSCT strategies and outcomes in individual paediatric ADs. We also provide a summary of the European Society for Blood and Marrow Transplantation (EBMT) Registry, where 343 HSCT procedures (176 autologous and 167 allogeneic) have been reported in 326 children (<18 years) for a range of AD indications. HSCT is a promising treatment modality, with potential long‐term disease control or cure, but therapy‐related morbidity and mortality need to be reduced. Further research is warranted to establish the position of HSCT in paediatric ADs via registries and prospective clinical studies to support evidence‐based interspeciality guidelines and recommendations.